Analisis Faktor-Faktor yang Mempengaruhi Kecurangan (Fraud) Ditinjau dari Fraud Hexagon di Kelurahan Kecamatan Mojoroto Kota Kediri - Meisa Nadiatul Fadliyah; Sigit Puji Winarko; Faisol Faisol (Journal Economic Excellence Ibnu Sina, 2025)
This study aims to determine the influence of factors in the fraud hexagon theory on the potential for fraud, which is described through the variables of compensation suitability, competence, organizational culture, effectiveness of internal control systems, and leadership style. Fraud hexagon theory is a development of the fraud triangle and fraud diamond theories, which emphasize six main elements that cause fraud, namely pressure, opportunity, rationalization, capability, arrogance, and collusion. This theory is relevant to describe various internal factors that can encourage fraudulent behavior, especially in the public sector. This study uses a quantitative approach with multiple linear regression analysis methods and is processed using SPSS software version 30. The population in this study are apparatus or village employees who work throughout the Mojoroto District, Kediri City. The sampling technique uses a purposive sampling method, with predetermined criteria. The selection process resulted in 42 respondents, consisting of the Village Head, Village Secretary, and Village Treasurer, who play important roles in administrative and financial management at the village level. Data were collected through closed-ended questionnaires distributed directly to respondents and analyzed to determine the relationship between the independent and dependent variables. The analysis results showed that partially, only the effectiveness of the internal control system and leadership style significantly influenced the potential for fraud. This indicates that strengthening the internal control system and transparent and accountable leadership can minimize fraudulent activities. Meanwhile, the variables of compensation suitability, competence, organizational culture, and unethical behavior did not show significant effects individually. However, simultaneously, all of these variables were proven to significantly influence the potential for fraud. Thus, fraud prevention must be carried out holistically by considering all aspects contained in the fraud hexagon theory.